Medidas de regulación para la explotación sostenible de Coryphaena hippurus "Perico" en el Perú - Solano Sare, Amado Abdías (2017)
ABSTRACT The fishery of Coryphaena hippurus "perico" has become one of most important activities of artisanal fleet in almost all ports and coves of Peru, especially in spring and summer, due to the resource accessibility. In the present work, database provided by the Statistics and Artisanal Fisheries Unit of IMARPE was used, in reference to Peruvian landings and artisanal fishing effort between 2000 and 2015. The information provided was statistical test of normality to determine if normal distribution, using the SPSS Program. The Shapiro-Wilk test, p (0,715) > 0,05 showed, with 95% of reliability that data have normal distribution. Based on the data processing, we obtained indicators of the status of Coryphaena hippurus, which served to develop regulatory measures that could be considered in "perico" fishery and thus, contribute to the sustainability of this Important resource. Based on the analysis of the results, the regulatory measures that could be considered in "perico" fishery would be: To establish an annual catch quota per fishing season (October - April) of 10 700 tones; to suspend the access of artisanal vessels to "perico" fishery for an indefinite period, in order to regulate the number of vessels. The hold capacity must not exceed 10 mt. The number of hooks per vessel will not be more than 1 500 units every hook will have the following characteristics: size No. 4, type J, the surface longline will be the only fishing gear and the maximum catch per boat-trip would no more than 3.00 t / v.